Perlindungan Hukum Terhadap Merek Dagang Nature Republic Terhadap Pemalsuan Merek Di Indonesia - Lidya Shinta Audina (Lentera Hukum, 2016)
Legal protection against the Nature Republic trademark against brand fraud based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications can be carried out through brand registration as stated in Article 4, Article 5, Article 6, Article and Article 8 of the Trademark Law. while repressive legal protection is obtained through a lawsuit for the deletion and cancellation of trademark registration where the trademark owner has the right to file the deletion and cancellation of the trademark registration violation, whereby registered trademark holders have the right to bring the dispute to criminal law based on article 101, article 101, article 102 and article 103 of Law Number 20 of 2016 concerning Trademarks and Geographical Indications as a complaint offense. The thing that happened in the Nature Republic brand can be said as an act of brand fraud because brand counterfeiting occurs when a fake product or a lower quality product is attached to a well-known brand. Therefore, Nature Republic brand owners request that companies that have used the Nature Republic brand without their permission to stop all production activities of goods and withdraw all of their production items that have been on the market. KEYWORDS: Legal Protection, Brand, Dispute Resolution Efforts.